Pregunta
upstudy study bank question image url

Solve \[ x^{3}-9 x^{2}+324=36 x \]

Ask by Logan Morrison. in the United States
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are \(x=-6\), \(x=6\), and \(x=9\).

Solución

Solve the equation \( x^{3}-9x^{2}+324=36x \). Solve the equation by following steps: - step0: Solve for \(x\): \(x^{3}-9x^{2}+324=36x\) - step1: Move the expression to the left side: \(x^{3}-9x^{2}+324-36x=0\) - step2: Factor the expression: \(\left(x-9\right)\left(x-6\right)\left(x+6\right)=0\) - step3: Separate into possible cases: \(\begin{align}&x-9=0\\&x-6=0\\&x+6=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=9\\&x=6\\&x=-6\end{align}\) - step5: Rewrite: \(x_{1}=-6,x_{2}=6,x_{3}=9\) The solutions to the equation \(x^{3}-9x^{2}+324=36x\) are \(x=-6\), \(x=6\), and \(x=9\).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve the equation \[ x^{3} - 9x^{2} + 324 = 36x, \] we first rearrange all terms to one side: \[ x^{3} - 9x^{2} - 36x + 324 = 0. \] Next, we can use the Rational Root Theorem or test for possible rational roots by substituting various integer values. Let's try \(x = 12\): \[ 12^{3} - 9(12^{2}) - 36(12) + 324. \] Calculating step-by-step: - \(12^{3} = 1728\) - \(9(12^{2}) = 9 \times 144 = 1296\) - \(36(12) = 432\) Now substituting these values into the polynomial: \[ 1728 - 1296 - 432 + 324 = 1728 - 1728 = 0. \] So, \(x = 12\) is indeed a root. Now, we can factor \(x - 12\) out of the cubic polynomial using synthetic division. Performing synthetic division of \(x^3 - 9x^2 - 36x + 324\) by \(x - 12\): \[ \begin{array}{r|rrrr} 12 & 1 & -9 & -36 & 324 \\ & & 12 & 36 & 0 \\ \hline & 1 & 3 & 0 & 324 \\ \end{array} \] The quotient is \(x^{2} + 3x + 27\). Therefore, we can express the cubic as: \[ (x - 12)(x^2 + 3x + 27) = 0. \] To find the remaining roots, we need to solve: \[ x^2 + 3x + 27 = 0. \] Using the quadratic formula \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\) with \(a = 1\), \(b = 3\), and \(c = 27\): Calculating the discriminant: \[ b^2 - 4ac = 3^2 - 4 \times 1 \times 27 = 9 - 108 = -99. \] Since the discriminant is negative, the quadratic has no real roots. Thus, we summarize the solution as follows: The real solution is \(x = 12\) and the other two roots are complex, found from \[ x = \frac{-3 \pm \sqrt{-99}}{2} = \frac{-3 \pm 3i\sqrt{11}}{2}. \] Final solutions: \[ \boxed{12}, \; \frac{-3 + 3i\sqrt{11}}{2}, \; \frac{-3 - 3i\sqrt{11}}{2}. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad